Digital online Learning by Using Digital Storytelling for Pre-Service Teacher Students - Sri Yuliani; Dicki Hartanto (International Journal of Language Education, 2022)
The purpose of this research discusses 1) to design a Digital storytelling in online learning, 2) to study the implementation of teaching English by using digital storytelling, and 3) to find out the practicality of digital storytelling for pre-service teacher students. This research is using design based research development model developed by Alessi and Trollip (2001) which consists of three stages, first stage is Planning, second stage is Design, and third is Development which focuses on designing digital storytelling to find more about the impact of digital storytelling as an online learning media process for English teaching material. The sample was 180 junior high students to get the need analysis data, 8 pre-service teacher students implemented the digital storytelling in the online classroom and two evaluators to access the appropriateness of digital storytelling to be used by pre-service teachers. As it is found in this research that designing digital storytelling showed practically on how a digital storytelling was designed, developed and applied in English class. The implementation of digital storytelling was successfully done by the pre-service students and the appropriateness was high which can be used in online teaching process.